OPTIMIZING STRATEGIES FOR RECURRENT VENTRAL HERNIA REPAIR - Zukhurov, S.E.; Bobov, K.Kh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Recurrent ventral hernias in elderly patients remain a significant clinical problem due to anatomical deterioration, reduced tissue quality, and the cumulative effects of previous surgical interventions. Conventional repair strategies often lack personalization and fail to address the specific risks in this vulnerable patient group. This review presents the rationale, structure, and clinical outcomes of a risk-based, anatomy-informed surgical algorithm for laparoscopic repair of recurrent ventral hernias in elderly and senile patients. Based on a cohort of 176 individuals, including both retrospective and prospective groups, a three-level scoring model was developed to guide the choice of surgical access, mesh type, and fixation method. Implementation of the model led to improved outcomes, including a significant reduction in recurrence and postoperative complications. Literature comparisons support the need for integrating individualized strategies into standard surgical practice for this high-risk population.